Comparative Study of ASEAN Tariff Profiles - Chulia J. Azarcon (Philippine Institute for Development Studies (PIDS), 1997)
Contrary to earlier findings, tariffs in most favored nations have significantly declined by as much as 51 percent since 1986. Nevertheless, the obduracy of some sectors to remain behind the protective tariffs and the existence of non-trade barriers still remain to be hurdled. Key strategy in Common Effective Preferential Tariff implementation includes transparency. Sectors and sub-sectors that are likely candidates for further trade liberalization are identified.
Keywords: 330; preferential tariff; unilateral trade reforms; specific tariff duties; trade-weighted averages; simple-weighted averages; General Agreement on Tariff and Trade; ASEAN